Land-use evolution in the catchment of Lake Murten, Switzerland. (15th February 2020) - Haas, Mischa; Kaltenrieder, Petra; Ladd, S. Nemiah; Welte, Caroline; Strasser, Michael; Eglinton, Timothy Ian; Dubois, Nathalie
Abstract: Anthropogenic soil erosion is a problem of global concern and recently has become the focus of extensive research. In spite of this, our knowledge about the history of land-use and its long-term impact on soil erosion and the local environment remains limited. This study seeks to address this issue by investigating sediments of Lake Murten, Switzerland, using a multi-proxy approach to reconstruct the history of land-use and its impacts in the catchment. We analyzed pollen and charcoal to reconstruct past land-use and vegetation dynamics, and used the distributions of terrestrial leaf wax biomarkers, their δ 13 C isotopic composition and their soil retention time (compound-specific 14 C) to evaluate long-term effects on past soil carbon dynamics. Arboreal pollen abundances, charcoal influx and cultural indicators match the archaeological evidence and reveal an eventful past around the lake. The first signs of human presence were detected around 5000 BCE, when Neolithic pile dwellers occupied the lake's shores. However, human land-use had no significant effect on the pollen and the sedimentary organic matter (OM) composition during Neolithic times and the Bronze Age. This changed during the Late Iron Age and the Early Roman Period (ca. 70 BCE). Coincident with the rise of Aventicum, a Roman city, large-scale deforestation and agriculture began in the region. Severe soil degradation and outwash of soil organic carbon (SOC) at this time is documented by enhanced input of soil-derived and pre-aged leaf waxes, and resulted in cultural eutrophication ca. 2000 years ago. Soil erosion decreased after the fall of the Roman Empire and a short period of renaturation followed. Although the export of SOC returned to pre-Roman values after ca. 200 years, the forest never recovered to its past extent. The last two detected periods of land-use change correlate with the onset of Medieval agriculture (ca. 1000 CE) and the Industrial Period (ca. 1800 CE). Today, the mean transit time of leaf waxes is almost five times longer compared to the Roman Period, suggesting that substantial soil erosion has occurred and that an even longer time period would be necessary for the soil carbon dynamics to recover to their natural state. Highlights: Pollen and leaf waxes from Lake Murten record land-use evolution since prehistory. Large-scale Roman deforestation and farming around the city of Aventicum. Land-use and vegetation recovery times following Roman disturbance took centuries.